Live Coding A User's Manual - Blackwell, Alan F. (Software Studies, 2022)
The first comprehensive introduction to the origins, aspirations, and evolution of live coding. Performative, improvised, on the fly: live coding is about how people interact with the world and each other via code. In the last few decades, live coding has emerged as a dynamic creative practice, gaining attention across cultural and technical fields-from music and the visual arts to computer science. Live Coding: A User's Manual is the first comprehensive introduction to the practice and a broader cultural commentary on the potential for live coding to open up deeper questions about contemporary cultural production and computational culture. This multiauthored book-by artists and musicians, software designers, and researchers-provides a practice-focused account of the origins, aspirations, and evolution of live coding, including expositions from a wide range of live coding practitioners. In a more conceptual register, the authors consider liveness, temporality, and knowledge in relation to live coding, alongside speculating on the practice's future forms. To freely download and read ebook (mobi, epub) and PDF files, please visit the resources tab. This book is open access and can be freely downloaded, shared and (if you wish) edited, subject to a CC-BY-SA license.